New approach for self-parking management system - Lahdili, Hicham; El Abidine Alaoui Ismaili, Zine (International Journal of Engineering and Technology, 2018)
The parking operation is considered the most stressful task amongst all driving experiences, and during this operation a considerable number of accidents are occurring each day. As a result, Parking Assistance Solutions (PAS) are widely used nowadays. Unfortunately, those systems are not fully automated and their role is limited to assisting the driver during the parking operation. This paper presents a proposal of a low cost, fully automated self-parking management solution. This proposal is a combination of two subsystems that will be collaborating to achieve a fully automated system; the first part is composed of an indoor navigation system, based on the adaptation of the available surveillance camera network in the parking area. This system will locate vehicles in the parking area and provide their current position in real time. And based on the localization information in addition to available free parking lots a server will generate navigation consigns. Those consigns (speed, rotation angle and direction) will be used by an auto-parking kit (that represent the second part of our proposal) to control the parking vehicle, that will drive itself to its reserved place.Â Â